Elevated Aminotransferase Activity as an Indication of Muscular Dystrophy: Case Reports and Review of the Literature - S Zamora; C Adams; JD Butzner; H Machida; Rb Scott (Canadian Journal of Gastroenterology)
Five male children are reported in whom incidental recognition of elevated serum alanine aminotransferase (ALT) activity initiated investigation to identify the cause of suspected hepatocellular injury. All five were later diagnosed with X chromosome-linked muscular dystrophy. The serum level of ALT, generally considered to be specific for hepatocellular injury, was increased two to 25 times above normal in all the reported cases. Paradoxically, the increase in ALT activity was greater than that of serum aspartate aminotransferase (three to 16 times normal), an enzyme whose elevation is generally recognized as being less specific and indicative of muscle, cardiac, kidney, pancreatic, red blood cell or hepatic injury. At presentation to the gastrointestinal service, one case, age 2.5 months, had no symptoms or signs of neuromuscular dysfunction, while the other four had previously unrecognized hypertrophy of the calves, proximal limb weakness, positive Gower’s sign or delayed gross motor skills. All five patients had marked elevation of serum creatine kinase activity and histopathologically confirmed muscular dystrophy. The practical clinical implication of this report is that children with elevated serum ALT, in the absence of other signs and symptoms of hepatic injury, may have occult muscular disease - most frequently muscular dystrophy. Although the clinical signs of muscular dystrophy may be subtle or absent, early determination of creatine kinase will suggest the correct diagnosis and minimize extensive and invasive investigation focusing on hepatic injury.